FAKE NEWS, THE EFFECTS OF SOCIAL MEDIA - Xoldarova Sarvinoz; To’raxon Abduraxmonov (TADQIQOTLAR, 2025)
Annotation:This text examines the growing influence of fake news and social media on modern society. It begins by defining fake news and explaining its various forms, such as fabricated stories, misleading content, manipulated visuals, and satire taken out of context. The text highlights the severe social consequences of misinformation, including fear, distrust, political manipulation, damaged reputations, and threats to public health. It then explores the positive impact of social media, including improved communication, educational opportunities, business development, and community building. At the same time, it presents the darker side of social platforms—addiction, reduced productivity, mental health issues, cyberbullying, privacy risks, and unrealistic social comparison. The text also explains why fake news spreads rapidly, noting psychological biases, economic motives, political agendas, and advanced technologies like deepfakes. In conclusion, the author emphasizes that while digital tools can be powerful, their impact depends largely on users’ responsibility, critical thinking, and awareness. By making informed choices, society can harness technology for unity, truth, and progress rather than division and deception.